A new species and a new geographical record of Calyptranthes (Myrcia s.l., Myrtaceae) from Brazil - Lourenço, Ana; Alves, Marccus (Phytotaxa, 2014)
Taxonomic studies on Calyptranthes have led to the identification and proposal of a new species, Calyptranthes serrana, endemic to the Atlantic rainforest. It is mainly characterized by its orbicular to orbicular-elliptic and coriaceous leaf blades, with abruptly acuminate apices, and 6–7 mm long buds. It is here described and illustrated, with comments concerning its distribution and habitat of occurrence. Considering the data available, the species is recognized as Endangered (EN) according to the IUCN criteria. Calyptranthes dryadica, a species previously considered as endemic to the state of São Paulo, is here registered for the state of Espírito Santo.